Relationship between Cognitive Performance and Depressive Symptoms in Chinese Older Adults: The China Health and Retirement Longitudinal Study (CHARLS) - Zhou, Lina; Ma, Xiancang; Wang, Wei (Journal of affective disorders, 2021)
lLower education, higher CESD-10 score, increased age, and more negative marital status were associated with poor cognitive performance in Chinese elderly.lCESD-10 is negatively correlated with each MMSE item, including orientation, memory, attention and computation, and language. In China, an increasing number of people are aging; therefore, attention should be paid to age-related cognitive impairment. With the increasing attention given to geriatric depression in recent years, we focused our investigation on the relationship between depression in the elderly and cognitive decline in a large Chinese community study. We screened 4,771 subjects that met the inclusion criteria from the China Health and Retirement Longitudinal Study database. Depressive symptoms and cognitive performance were assessed using the 10-item Center for Epidemiological Studies Depression Scale (CESD-10) and Mini-Mental State Examination (MMSE), respectively. We found that 4.46% of the elderly have depression and 35.19% have depressive symptoms. Lower education, higher CESD-10 score, increased age, and more negative marital status were associated with poor cognitive performance in the Chinese elderly. CESD-10 is negatively correlated with each MMSE item, including orientation, memory, attention and computation, and language. It was difficult to draw conclusions about causation since there was no follow-up data, and high CESD-10 scores do not represent the population study finally diagnosed with depression. Finally, it is not clear whether the decline in cognitive function had an impact on participants’ understanding of the problems in the CESD-10. This study preliminary prompted severe depressive symptoms associated with worse cognitive performance in a Chinese elderly community population.